Role Model Exemplarity As An Effective Strategy For Internalizing Anti-Corruption Values - Inge Angelia; Naufal Raid; Guesa Maiwinda; Silvia Anggreni BP (The Future of Education Journal, 2026)
This study aimed to examine the relationship between role model exemplary behavior and the internalization of anti-corruption values among university students. A quantitative correlational approach was employed involving 194 students as research participants. Data were collected through questionnaires and analyzed using descriptive statistics and Pearson correlation analysis. The results revealed a positive and significant relationship between role model exemplary behavior and the internalization of anti-corruption values (r = 0.693; p < 0.001), indicating a strong correlation. These findings suggest that the higher the level of exemplary behavior demonstrated by lecturers as role models, the higher the level of anti-corruption values internalized by students. Therefore, lecturers’ exemplary behavior plays an important role in strengthening anti-corruption education in higher education institutions.